Peramalan Cuaca Menggunakan Metode Rantai Markov (Studi Kasus : Cuaca Harian Di Kota Ambon) - Sasake, Set; Lesnussa, Yopi Andry; Wattimena, Abraham Zakaria (Jurnal Matematika, 2021)
Weather is a state of the air at certain times in certain areas that are relatively narrow and in a short period of time. Weather forecasting is an activity carried out to produce a collection of information about upcoming weather conditions. One method used to predict these conditions is by using the Markov chain method. The Markov chain is a random process in which all information about the future is contained in the present state. The purpose of this study is to model and predict daily weather that will occur over the next week with the Markov Chain model. The data used in this study are Ambon City daily weather data from December 1, 2019, to January 31, 2020, by the Meteorology, Climatology, and Geophysics Agency (BMKG), Ambon City Meteorological Station. Daily weather forecasting results that occur are quite varied but the most dominant weather occurs during the next week that is Cloudy and Light Rain.